2011
DOI: 10.1089/cell.2011.0032
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitor Significantly Improved the Cloning Efficiency of Porcine Somatic Cell Nuclear Transfer Embryos

Abstract: Valproic acid (VPA), a histone deacetylase inbibitor, has been shown to generate inducible pluripotent stem (iPS) cells from mouse and human fibroblasts with a significant higher efficiency. Because successful cloning by somatic cell nuclear transfer (SCNT) undergoes a full reprogramming process in which the epigenetic state of a differentiated donor nuclear is converted into an embryonic totipotent state, we speculated that VPA would be useful in promoting cloning efficiency. Therefore, in the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 43 publications
4
29
1
Order By: Relevance
“…Since then, many other HDACis, such as Scriptaid, valproic acid (VPA), or oxamflatin, have been applied to SCNT protocols to enhance reprogramming and increase cloning rates (Van Thuan et al, 2010;. VPA, for instance, is a short-chain fatty acid with HDACi activity that has proved to increase development and quality of mouse, bovine, and porcine SCNT embryos to a similar or even higher extent than TSA (Costa-Borges et al, 2010;Huang et al, 2011;Isaji et al, 2013;Kim et al, 2011;Miyoshi et al, 2010;Xu et al, 2012). Although the effects of each particular HDACi may vary among strains and species and some of the tested HDACis, such as aroyl pyrrolyl hydroxamide, have shown no beneficial effects (Van Thuan et al, 2009), it is clear from numerous reports that most HDACis improve nuclear reprogramming and cloning efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, many other HDACis, such as Scriptaid, valproic acid (VPA), or oxamflatin, have been applied to SCNT protocols to enhance reprogramming and increase cloning rates (Van Thuan et al, 2010;. VPA, for instance, is a short-chain fatty acid with HDACi activity that has proved to increase development and quality of mouse, bovine, and porcine SCNT embryos to a similar or even higher extent than TSA (Costa-Borges et al, 2010;Huang et al, 2011;Isaji et al, 2013;Kim et al, 2011;Miyoshi et al, 2010;Xu et al, 2012). Although the effects of each particular HDACi may vary among strains and species and some of the tested HDACis, such as aroyl pyrrolyl hydroxamide, have shown no beneficial effects (Van Thuan et al, 2009), it is clear from numerous reports that most HDACis improve nuclear reprogramming and cloning efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Given the results of more recent studies, higher VPA concentrations and/or longer treatment durations could further increase the beneficial effects of VPA (Huang et al, 2011;Isaji et al, 2013;Kim et al, 2011;Xu et al, 2012). Therefore, in the first part of the study, we sought to determine the optimal concentration and treatment duration for both PsA and VPA in terms of in vitro development of cloned mouse embryos and blastocyst quality.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when ESCs were synchronized to metaphase, a stage of cell cycle equivalent with metaphase II (MII) stage of matured oocyte, their cytoplast had the capacity to reprogram somatic cells (Du et al 2011). In addition, pretreatment of somatic cell with some small molecules, such as valproic acid (VPA), butyrate, and 5-aza-2′-deoxycytidine (AZA), could improve both the efficiency of SCNT and iPSCs Huangfu et al 2008;Mikkelsen et al 2008;Mali et al 2010;Huang et al 2011;Liu et al 2012). Furthermore, cell-free extracts from either oocytes or ESCs could be used to reprogram somatic cells (Taranger et al 2005;Miyamoto et al 2009).…”
Section: Matured Oocytes Were Endowed With Totipotent Developmental Pmentioning
confidence: 99%
“…For example, Li et al (2008) observed a delay in SCNT pig morula compaction when embryos were treated with the HDACi trichostatin A (TSA). In contrast, Dai et al (2010) described that the onset of cavitation occurred earlier in SCNT mouse embryos treated with the HDACi m-carboxycinnamic acid bishydroxamide, and Huang et al (2011a) reported that SCNT pig embryos treated with the HDACi valproic acid (VPA) reached the blastocyst stage earlier than non-treated ones.…”
Section: Introductionmentioning
confidence: 99%